Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 25 May 2017, 19:11

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If q is one root of the equation x^2 + 18x + 11c = 0, where

Author Message
TAGS:

### Hide Tags

Director
Joined: 03 Sep 2006
Posts: 875
Followers: 7

Kudos [?]: 893 [2] , given: 33

If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

24 Oct 2012, 04:43
2
KUDOS
9
This post was
BOOKMARKED
00:00

Difficulty:

35% (medium)

Question Stats:

67% (02:30) correct 33% (01:39) wrong based on 299 sessions

### HideShow timer Statistics

If q is one root of the equation x^2 + 18x + 11c = 0, where –11 is the other root and c is a constant, then q^2-c^2 =

A) 98
B) 72
C) 49
D) 0
E) It can't be determined from the information given
[Reveal] Spoiler: OA

Last edited by Bunuel on 24 Oct 2012, 05:02, edited 1 time in total.
Renamed the topic and edited the question.
Math Expert
Joined: 02 Sep 2009
Posts: 38889
Followers: 7735

Kudos [?]: 106146 [0], given: 11607

### Show Tags

24 Oct 2012, 05:08
Expert's post
9
This post was
BOOKMARKED
LM wrote:
If q is one root of the equation $$x^2 + 18x + 11c = 0$$, where –11 is the other root and c is a constant, then $$(q^2)-(c^2) =$$

A) 98
B) 72
C) 49
D) 0
E) It can't be determined from the information given

Viete's theorem states that for the roots $$x_1$$ and $$x_2$$ of a quadratic equation $$ax^2+bx+c=0$$:

$$x_1+x_2=\frac{-b}{a}$$ AND $$x_1*x_2=\frac{c}{a}$$.

Thus according to the above $$x_1+x_2=q+(-11)=\frac{-18}{1}$$ --> $$q=-7$$ AND $$x_1*x_2=(-7)*(-11)=\frac{11c}{1}$$ --> $$c=7$$.

$$q^2-c^2 =(-7)^2-7^2=0$$.

Hope it's clear.
_________________
Intern
Status: wants to beat the gmat
Joined: 18 Jul 2012
Posts: 20
Location: United States
Followers: 0

Kudos [?]: 9 [1] , given: 1

### Show Tags

24 Oct 2012, 15:24
1
KUDOS
Bunuel wrote:
LM wrote:
If q is one root of the equation $$x^2 + 18x + 11c = 0$$, where –11 is the other root and c is a constant, then $$(q^2)-(c^2) =$$

A) 98
B) 72
C) 49
D) 0
E) It can't be determined from the information given

Viete's theorem states that for the roots $$x_1$$ and $$x_2$$ of a quadratic equation $$ax^2+bx+c=0$$:

$$x_1+x_2=\frac{-b}{a}$$ AND $$x_1*x_2=\frac{c}{a}$$.

Thus according to the above $$x_1+x_2=q+(-11)=\frac{-18}{1}$$ --> $$q=7$$ AND $$x_1*x_2=7*(-11)=\frac{11c}{1}$$ --> $$c=-7$$.

$$q^2-c^2 =7^2-(-7)^2=0$$.

Hope it's clear.

shouldn't q = -7 and c = 7?
Math Expert
Joined: 02 Sep 2009
Posts: 38889
Followers: 7735

Kudos [?]: 106146 [0], given: 11607

### Show Tags

24 Oct 2012, 17:09
watwazdaquestion wrote:
Bunuel wrote:
LM wrote:
If q is one root of the equation $$x^2 + 18x + 11c = 0$$, where –11 is the other root and c is a constant, then $$(q^2)-(c^2) =$$

A) 98
B) 72
C) 49
D) 0
E) It can't be determined from the information given

Viete's theorem states that for the roots $$x_1$$ and $$x_2$$ of a quadratic equation $$ax^2+bx+c=0$$:

$$x_1+x_2=\frac{-b}{a}$$ AND $$x_1*x_2=\frac{c}{a}$$.

Thus according to the above $$x_1+x_2=q+(-11)=\frac{-18}{1}$$ --> $$q=7$$ AND $$x_1*x_2=7*(-11)=\frac{11c}{1}$$ --> $$c=-7$$.

$$q^2-c^2 =7^2-(-7)^2=0$$.

Hope it's clear.

shouldn't q = -7 and c = 7?

Sure. Typo edited. Thank you. +1.
_________________
GMAT Club Legend
Joined: 09 Sep 2013
Posts: 15448
Followers: 649

Kudos [?]: 209 [0], given: 0

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

17 Aug 2014, 10:09
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
Current Student
Joined: 16 Jan 2014
Posts: 44
Followers: 1

Kudos [?]: 13 [0], given: 36

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

15 Sep 2014, 14:19
The way I approached this question is as follows:

1) If one root is -11 then using the rule of factoring: (x+11)(x+7)=0, q=-7, c=7
2) Since q^2-c^2=(q+c)(q-c), (q+c)=-7+7=0, q^2-c^2=0
Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 7374
Location: Pune, India
Followers: 2288

Kudos [?]: 15113 [2] , given: 224

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

15 Sep 2014, 22:09
2
KUDOS
Expert's post
LM wrote:
If q is one root of the equation x^2 + 18x + 11c = 0, where –11 is the other root and c is a constant, then q^2-c^2 =

A) 98
B) 72
C) 49
D) 0
E) It can't be determined from the information given

Another method to solve it is - plug the root that is available to get the value of c.

$$(-11)^2 + 18*(-11) + 11c = 0$$
$$c = 7$$

So the equation becomes $$x^2 + 18x + 77 = 0$$ which gives x = -7 or -11.
So q must be -7.
$$(-7)^2 - 7^2 = 0$$

_________________

Karishma
Veritas Prep | GMAT Instructor
My Blog

Get started with Veritas Prep GMAT On Demand for \$199

Veritas Prep Reviews

CEO
Joined: 17 Jul 2014
Posts: 2502
Location: United States (IL)
Concentration: Finance, Economics
Schools: Stanford '19 (D)
GMAT 1: 650 Q49 V30
GPA: 3.92
WE: General Management (Transportation)
Followers: 26

Kudos [?]: 342 [0], given: 168

If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

16 Sep 2014, 13:57
one way to solve it really fast is to factor it:
x=-11 thus we get (x+11)
in order to get x^2+18x+11c=0, q must be also a negative, otherwise we cannot get to this equation, therefore we get x+q

now we can factor (x+q)(x+11)=0
q+11=18
q*11=11c

since we need q^2-c^2, because every number squared to an even power is a positive number, 11q=11c=>q^2=c^2, and therefore q^2-c^2=0!
SVP
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1857
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Followers: 51

Kudos [?]: 2170 [0], given: 193

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

22 Sep 2014, 02:44
LM wrote:
If q is one root of the equation x^2 + 18x + 11c = 0, where –11 is the other root and c is a constant, then q^2-c^2 =

A) 98
B) 72
C) 49
D) 0
E) It can't be determined from the information given

$$x^2 + 18x + 11c = 0$$

$$x^2 + (11 + 7)x + (11 * c) = 0$$

c = 7

Given one root = -11, so other root = -7 = q

$$c^2 - q^2 = 49 - 49 = 0$$

_________________

Kindly press "+1 Kudos" to appreciate

Director
Joined: 10 Mar 2013
Posts: 597
Location: Germany
Concentration: Finance, Entrepreneurship
GMAT 1: 580 Q46 V24
GPA: 3.88
WE: Information Technology (Consulting)
Followers: 17

Kudos [?]: 356 [0], given: 200

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

05 May 2015, 13:51
We have roots q and -11, so using vieta's theorem X1*X2 = C --> q*(-11) = 11c -> q = -c then q^2 - c^2 = 0
_________________

When you’re up, your friends know who you are. When you’re down, you know who your friends are.

800Score ONLY QUANT CAT1 51, CAT2 50, CAT3 50
GMAT PREP 670
MGMAT CAT 630
KAPLAN CAT 660

GMAT Club Legend
Joined: 09 Sep 2013
Posts: 15448
Followers: 649

Kudos [?]: 209 [0], given: 0

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

27 Jun 2016, 18:38
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
Intern
Joined: 13 Aug 2016
Posts: 2
Followers: 0

Kudos [?]: 0 [0], given: 0

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

19 Feb 2017, 12:44
(x+11)(x+q) = 0

11+q = 18
q= 7
11*q = 77
11*c = 77
c=7
q^2 -c^2 =(-7)^2 - 7^2 = 0
Director
Joined: 07 Dec 2014
Posts: 670
Followers: 3

Kudos [?]: 137 [0], given: 3

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

19 Feb 2017, 16:13
LM wrote:
If q is one root of the equation x^2 + 18x + 11c = 0, where –11 is the other root and c is a constant, then q^2-c^2 =

A) 98
B) 72
C) 49
D) 0
E) It can't be determined from the information given

if q and -11 are roots,
then (x-q)(x+11)=x^2-qx+11x-11q=0
-qx+11x=18x
q=-7
-11q=11c
c=7
(-7)^2-7^2=0
Manager
Status: Preparing for GMAT!!
Joined: 11 Oct 2015
Posts: 123
Location: India
GMAT 1: 660 Q47 V34
GPA: 3.1
WE: General Management (Consumer Products)
Followers: 0

Kudos [?]: 13 [0], given: 103

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where [#permalink]

### Show Tags

24 Feb 2017, 12:08
LM wrote:
If q is one root of the equation x^2 + 18x + 11c = 0, where –11 is the other root and c is a constant, then q^2-c^2 =

A) 98
B) 72
C) 49
D) 0
E) It can't be determined from the information given

Product of roots=c/a
=> $$q*-11=\frac{11c}{1}$$
=>$$c=-q$$

$$q^2-c^2=q^2-(-q)^2=q^2-q^2=0$$
_________________

Yours,
Siva Rama Krishna Meka

Re: If q is one root of the equation x^2 + 18x + 11c = 0, where   [#permalink] 24 Feb 2017, 12:08
Similar topics Replies Last post
Similar
Topics:
1 If -4 is one solution to the equation x^2+bx+c=0,where b and c 4 23 Apr 2017, 22:21
2 If one of the roots of the quadratic equation x^2 + mx + 24 = 0 is 1.5 4 15 Jun 2016, 04:19
3 If one root of the equation x 2 − 5x + m = 0 is 10, what is the value 3 15 Jun 2016, 04:07
4 If one root of the equation 2x^2 + 3x – k = 0 is 6, what is the value 6 22 Aug 2015, 05:28
21 If one root of x^2+px+12=0 is 4, and the equation x^2+px+q=0 12 22 Oct 2016, 12:17
Display posts from previous: Sort by